Migration shocks and voting: Evidence from Ukrainian migration to Poland - Dariia Mykhailyshyna; David Zuchowski (Global Labor Organization (GLO), 2025)
This paper examines the impact of two massive and unexpected inflows of Ukrainians on voting behavior in Poland. The two migration shocks, caused by Russia's aggression against Ukraine in 2014 and 2022, allow us to compare the effects of conflict-induced labor migration and those of refugee inflows. Using an instrumental variable approach, we find that greater exposure to labor migrants reduces support for conservative parties in the short run and subsequently shifts voter preferences toward pro-redistribution parties. We do not find similar effects for refugees, who, unlike temporary labor migrants, had access to social benefits. Exposure to both types of Ukrainian migration leads to a decrease in far-right voting. This effect emerges only after the salience of Ukrainian migrants increases due to the escalation of Russia's aggression and the rise of anti-Ukrainian rhetoric from the Polish far-right. The backlash from Polish voters against the far-right rhetoric is ten times stronger in areas exposed to refugees than to labor migrants. Our results are robust to the use of a number of instruments and several sensitivity checks.
Keywords: D72; F22; J61; P16; R23; 330; Immigration; Refugees; Political Economy; Voting; Poland; Ukraine